The foundations of colonial self-government - O'Connell, John Robert (Statistical and Social Inquiry Society of Ireland, 1917)
The assembling of representatives of the self-governing Dominions and of India for the Second Imperial Conference, which is now taking place in London, has suggested to me the propriety of inviting the attention of this Society to the foundations and development of the constitutions of the self-governing Communities of the Empire and their relations, both fiscal and constitutional, with the Imperial Government. I approach this inspiring subject with much diffidence, because I am conscious that some of the questions which present themselves require for their discussion a familiarity with constitutional law and principles and a knowledge of Colonial history, which I do not possess. In spite of these difficulties in my task, and conscious of my inability to discharge it adequately, I venture to lay before you this evening a summary of the constitutions under which what I may describe as our greater Colonies have made such amazing progress in population and in material prosperity, because it seems to me that there never was a time when full and accurate knowledge of the principles and development of Colonial Self-Government was so necessary as it is today.
Read, April 27th, 1917
Keywords: Self-government; British colonies; 314.15